Ethical issues of psychological expertise and interdisciplinary interaction between psychologists and lawyers - Shaboltas, A.V. (Psihologiâ i pravo, 2025)
Context and relevance. Effective law enforcement practice, including investigative and judicial actions, involves intensive interactions and collaboration of specialists of various profiles, which requires, in particular, a mutual understanding of the specifics of the work and the implementation of professional ethical standards by lawyers and psychologists. The most difficult problems are the ethical dilemmas and complexities in the field of judicial process and, in particular, the conduct and interpretation of the results of forensic psychological examination. Objective. Analysis of the ethical foundations and the most relevant ethical dilemmas in the field of forensic psychological examination practice and interaction between psychologists and lawyers. Methods and materials. Analysis of national and foreign literary sources, ethical regulation in the law enforcement practice of psychologists and lawyers, as well as materials of civil and criminal cases (100 cases concerning minors). Results. The most serious ethical problems for lawyers and psychologists working at the intersection of two applied disciplines in expert work are difficulties of a terminological and substantive nature, as well as understanding and implementing basic ethical principles and norms. Conclusions. Effective professional interaction and the resolution of ethical problems arising in the field of forensic psychological examination require active joint efforts of specialists in two fields - lawyers and psychologists both in terms of developing ethically sound interaction strategies and practical activities. Контекст и актуальность. Эффективная правоприменительная практика, включая следственные и судебные действия, предполагает интенсивное взаимодействие и сотрудничество специалистов разного профиля, которое требует, в частности, взаимного понимания специфики работы и реализации профессиональных этических норм юристами и психологами. Одними из самых сложных и трудных проблем являются этические дилеммы и сложности в области судебного процесса и, в частности, в проведении и трактовке результатов судебно-психологической экспертизы. Цель. Анализ этических основ и наиболее актуальных этических проблем в области практики судебно-психологической экспертизы и взаимодействия психологов и юристов. Методы и материалы. Анализ отечественных и зарубежных литературных источников, этического регулирования в правоприменительной практике психологов и юристов, а также материалов гражданских и уголовных дел (100 кейсов, касающихся несовершеннолетних лиц). Результаты. Наиболее серьезными этическими проблемами для юристов и психологов, работающих на пересечении двух прикладных дисциплин в экспертной деятельности, являются трудности терминологического и содержательного характера, а также понимания и реализации базовых этических принципов и норм. Выводы. Эффективное профессиональное взаимодействие и разрешение возникающих в области судебно-психологической экспертизы этических проблем требуют активных совместных усилий специалистов двух областей - юристов и психологов, как в части выработки этически обоснованных стратегий взаимодействия, так и в области практической деятельности.